2023
DOI: 10.1002/hpm.3633
|View full text |Cite
|
Sign up to set email alerts
|

Appraising war's impacts on neurosurgical delivery in Ukraine

Abstract: The conflict in Ukraine, which started when Russia invaded and violated its sovereignty, has led to the country's worst war since the annexation of Crimea in 2014. The war has resulted in a significant number of casualties, displaced millions of people, and damaged the healthcare system, which was already struggling before the conflict. The neurosurgical field, in particular, has been severely affected, with infrastructure and healthcare systems routinely demolished or interrupted in conflict zones, making fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
3
0
1
Order By: Relevance
“…Neben der stattgehabten SARS-CoV-2-Pandemie spielen zwischen Juni und September 2022 die militärischen Auseinandersetzungen in der Ukraine eine bedeutende Rolle für ukrainische Onkologen bei Ausübung ihrer Tätigkeit [30]. Ärztliches Handeln während bewaffneter Konflikte stellt eine besondere Herausforderung dar, weil insbesondere die Infrastruktur und die Gesundheitssysteme in den Konfliktgebieten routinemäßig zerstört oder unterbrochen wurden [79]. Ärzte erleb(t)en Übergriffe, Einschüchterungen, sogar Misshandlungen während sie allen Menschen ohne Diskriminierung helfen oder dieses taten [30].…”
Section: Diskussionunclassified
“…Neben der stattgehabten SARS-CoV-2-Pandemie spielen zwischen Juni und September 2022 die militärischen Auseinandersetzungen in der Ukraine eine bedeutende Rolle für ukrainische Onkologen bei Ausübung ihrer Tätigkeit [30]. Ärztliches Handeln während bewaffneter Konflikte stellt eine besondere Herausforderung dar, weil insbesondere die Infrastruktur und die Gesundheitssysteme in den Konfliktgebieten routinemäßig zerstört oder unterbrochen wurden [79]. Ärzte erleb(t)en Übergriffe, Einschüchterungen, sogar Misshandlungen während sie allen Menschen ohne Diskriminierung helfen oder dieses taten [30].…”
Section: Diskussionunclassified
“…Health care systems are essentially destroyed by war, resulting in more individuals without access to health care, particularly surgical care, and limited access to medical supplies. 2 , 3 Studies demonstrate that insufficient medical infrastructure and knowledge may profoundly impact the service grade. For instance, a study of 607 surgeons conducted in Tripoli, Libya, in 2014 and 2015 revealed that more than 81% of those polled claimed that insufficient hospital equipment made it difficult to successfully treat explosion injuries.…”
Section: Management Gaps On Cmft Surgical Deliverymentioning
confidence: 99%
“…Massive damage to their health care infrastructure led to the exodus of highly trained medical professionals, particularly surgeons, and economic devastation, making it challenging to uphold traditional health care standards. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation